Execução penal e o microsistema da tutela coletiva - Armede, Juliana Felicidade (2009)
The purpose of this study is to estabilish the relationship between collective interests and penal execution. The collective interests on penal execution cannot be comprehended as the sum of penal rights that reveals the execution penal system. It is also a purpose to show that is possible to take collective procedures measures in order to defend those interests, even though these measures are not estabilished in the Brazialin Penal Procedure system. These procedural measures are revealed by the brazilian collective action system, mainly the civil public action. It is also revealed by the international legal protection of human rights system, which allows International Boards to get in touch with complains. Yet, it was established that both systems, national and international, can be applied together, as far both of them are strictly related to penal execution